Putting Citizens First in Fragile and Conflict-Affected Situations : Open Development Missions to Afghanistan and Myanmar - Henvey, Kate (International Finance Corporation, Washington, DC, 2014)
How can the World Bank engage the principles of open development and accountability with our clients in fragile and conflict-affected situations (FCS)? With the support of our partners and counterparts in Afghanistan and Myanmar, the Bank convened governments and their citizens including media, civil society, students, and academia to discuss the Bank s Open Development initiative at public forums and to learn how to use Bank resources in focused trainings. It was clear that, while resources for accountability may be limited, the citizens were eager! This SmartLesson shares some of what we learned during Open Development missions organized by External and Corporate Relations Operational Communications.